Universality and Cultural Diversity in Moral Reasoning and Judgment - Bentahila, Lina; Fontaine, Roger; Pennequin, Valérie (Frontiers in Psychology, 2021)
Many theories have shaped the concept of morality and its development by anchoring it in the realm of the social systems and values of each culture. This review discusses the current formulation of moral theories that attempt to explain cultural factors affecting moral judgment and reasoning. It aims to survey key criticisms that emerged in the past decades. In both cases, we highlight examples of cultural differences in morality, to show that there are cultural patterns of moral cognition in Westerners’ individualistic culture and Easterners’ collectivist culture. It suggests a paradigmatic change in this field by proposing pluralist “moralities” thought to be universal and rooted in the human evolutionary past. Notwithstanding, cultures vary substantially in their promotion and transmission of a multitude of moral reasonings and judgments. Depending on history, religious beliefs, social ecology, and institutional regulations (e.g., kinship structure, economic markets) each society develops a moral system emphasizing several moral orientations. This variability raises questions for normative theories of morality from a cross-cultural perspective. Consequently, we shed light on future descriptive work on morality to identify the cultural characteristics likely to impact the expression or development of reasoning, justification, argumentation, and moral judgment in Westerners’ individualistic culture and Easterners’ collectivist culture.